Emergency Department Visits for Postpartum Hypertension [16I]. (May 2016) - Brousseau, Erin C.; Danilack, Valery A.; Cai, Fei; Matteson, Kristen A.
Abstract : INTRODUCTION: Hypertensive disorders have emerged as a leading cause for postpartum readmission. Understanding the characteristics of hypertensive women who present to the emergency department (ED) postpartum could facilitate the development of strategies to better deliver postpartum care and prevent readmission. METHODS: We reviewed the charts of a cohort of postpartum women presenting to the ED at a tertiary care women's hospital over a six-month period. Women with an ED diagnosis of hypertension were compared to women with all other ED diagnoses. RESULTS: Among 252 women who presented for ED care in the 42 days post-delivery, 52 were given an ED diagnosis of hypertension. Women with postpartum hypertension presented earlier and were more likely to be readmitted than women in the ED without hypertension (7.0 days [SD 4.3] compared to 12.7 [SD 10.0], P =.001 and 58% compared to 12%, P =.001, respectively). Additionally, women diagnosed with postpartum hypertension were more likely to have preexisting hypertension (RR 5.24, 95% CI 2.56–10.73), gestational hypertension (RR 2.61, 95% CI 1.59–4.29), preeclampsia (RR 3.85, 95% CI 2.11–7.00), or gestational diabetes (RR 2.16, 95% CI 1.01–4.61) compared to women in the ED without hypertension. Looking at clinical findings, women with postpartum hypertension were 2.85 times more likely to have had a blood pressure of greater than or equal to 140/90 during postpartum hospitalization (95% CI 2.12–3.83) when compared to other postpartum ED patients. CONCLUSION: Postpartum hypertension may have identifiable risk factors prior to hospital discharge. Given the early presentation and high rate of readmission for postpartum hypertension, future research should focus on identifying and managing women at risk.